"But will God indeed dwell on the earth?" God and Space. (20th April 2018) - Lehmkühler, Karsten
Abstract: The so‐called "spatial turn" has led to renewed interest in the question of space among theologians. Concerning the concept of divine omnipresence, classical positions (Aquinas, Luther) underlined that God is present in the created world through God's essence and creating power. Contemporary authors sometimes oppose a classic and pre‐Kantian "container model" and adopt preferentially a more modern "relational model" of space. This article argues that these two models are not mutually exclusive, and that an analogical approach, linking the "space of God" and "created space", might help us understand the encompassing presence of God in God's creation.